Concern, Cynicism, and the Coronavirus: Assessing the Influence of Instrumental and Normative Factors on Individual Defiance of COVID-19 Mitigation Guidelines - Moule, Richard K. (Crime & delinquency, 2022)
In the early stages of the COVID-19 pandemic, governments enacted guidelines to mitigate the spread of the coronavirus. Public defiance of these guidelines invoked instrumental concerns about the virus and normative concerns regarding government mandates and overreach during the pandemic. Drawing on normative and instrumental explanations for compliance with the law, the current study uses a national sample of 600 American adults surveyed during the beginning of the pandemic to examine defiance of these guidelines. Using structural equation modeling, we find that legal cynicism is positively associated with defiance, while fear and perceived severity of the coronavirus are negatively related to defiance. Findings suggest that fostering compliance with public health guidelines will involve reducing legal cynicism among the public.